2019
DOI: 10.1016/j.dadm.2018.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Actual memory as a mediator of the amyloid‐subjective cognitive decline relationship

Abstract: Introduction Amyloid pathology in cognitively normal adults is associated with subjective cognitive decline, potentially reflecting awareness of Alzheimer's-related memory deficits. To clarify the mechanism underlying this relationship, we used mediational analyses to determine the role of depression, anxiety, and actual memory performance. Methods To assess amyloid deposition, we imaged 85 cognitively normal adults with florbetapir positron emission tomography imaging.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 44 publications
2
19
0
Order By: Relevance
“…SCD was assessed in the DLBS using the Metamemory in Adulthood questionnaire (Chen, Farrell, Moore, & Park, 2019), however, this data has yet to be released. SCD was assessed in the DLBS using the Metamemory in Adulthood questionnaire (Chen, Farrell, Moore, & Park, 2019), however, this data has yet to be released.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SCD was assessed in the DLBS using the Metamemory in Adulthood questionnaire (Chen, Farrell, Moore, & Park, 2019), however, this data has yet to be released. SCD was assessed in the DLBS using the Metamemory in Adulthood questionnaire (Chen, Farrell, Moore, & Park, 2019), however, this data has yet to be released.…”
Section: Discussionmentioning
confidence: 99%
“…A potential limitation to this study is that we were unable to control for SCD. SCD was assessed in the DLBS using the Metamemory in Adulthood questionnaire (Chen, Farrell, Moore, & Park, 2019), however, this data has yet to be released. SCD has been related to mesiotemporal atrophy, functional connectivity alterations, decreased task-directed attention, and increased white matter hyperintensities (Fan et al, 2018;Hayes et al, 2017;Van Rooden et al, 2018;Verfaillie et al, 2018;Viviano et al, 2019), and might thus have been an interesting variable to relate to neocortical and hippocampal measures in the newly proposed gradient space.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that worried individuals with SCD have an increased risk of developing objective cognitive decline [6,28,29,77]. However, Chen, et al [62] recently showed that individuals with amyloid plaques, self-reported memory difficulties or memory concerns and not depression or anxiety, were associated with self-awareness of actual worsening in memory function [62]. In our sample, memory was the most frequent SCD complaint, regardless of help-seeking status.…”
Section: Discussionmentioning
confidence: 50%
“…As most SCD cases are benign, or not caused by degenerative brain disease [17], it has been suggested that SCD may be associated with depression, rather than preclinical AD [58,59]. While it has been reported that presentation of SCD may correlate with depression rather than objective cognitive decline [60,61], the link between SCD and depressive symptoms has not been universally supported [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…A potential limitation to this study is that we were unable to control for subjective cognitive decline (SCD). SCD was assessed in the DLBS using the Metamemory in Adulthood questionnaire (Chen, Farrell, Moore, & Park, 2019), however, this data has yet to be released. SCD has been related to mesiotemporal atrophy and functional connectivity changes (Fan et al, 2018;Verfaillie et al, 2018), and might thus have been an interesting variable to relate to neocortical and hippocampal measures in the newly proposed gradient space.…”
Section: Discussionmentioning
confidence: 99%